Resolving Wrongful Arrest Cases from a Victimological Perspective - Muhammad Rhogust; Martanti Endah Lestari; M. Afrizal (CV. RADJA PUBLIKA, 2026)
This study examines the resolution of wrongful arrest cases from a victimological perspective, particularly in light of the changes introduced by Law of the Republic of Indonesia Number 20 of 2025 concerning the Criminal Procedure Code. These changes reflect a shift from procedural justice toward a more substantive and human rights-oriented approach. The study aims to analyze the legal mechanisms for resolving wrongful arrest cases and to identify the rights and obligations of the state toward victims. This research employs a normative legal research method, utilizing statutory, conceptual, and case approaches. Data are derived from primary and secondary legal materials, including legislation and relevant literature, which are analyzed descriptively and qualitatively. The findings indicate that the new Criminal Procedure Code provides stronger legal protection for victims of wrongful arrest through mechanisms such as compensation and rehabilitation. Compensation is no longer merely procedural but serves as a substantive instrument of justice, encompassing material and immaterial losses. Furthermore, the state bears responsibility for fulfilling victims’ rights as part of its obligation to uphold human rights and ensure justice. In conclusion, the legal framework governing wrongful arrest in Indonesia has evolved toward a more victim-oriented approach, emphasizing restoration, accountability, and the prevention of future violations.